A professional development analysis for Turkish language teachers: What did they expect? What have they found? - Hatice Yurtseven Yılmaz; Sedat Sever (Journal of Pedagogical Research, 2021)
Professional development studies have contributed to teachers' professional motivation and student success. Therefore, professional development activities must take into account the needs and interests of the stakeholders involved in education circles. The current study aims to examine Turkish language teachers' past experiences with professional development and determine their perceptions of and expectations from professional development. The study adopted a phenomenological approach. The data were collected from interviews conducted with 38 Turkish language teachers working in Bursa. The data were analyzed qualitatively using content analysis. Findings showed that the Turkish language teachers were keen to participate in the professional development activities held by the Ministry of National Education (MONE) in Turkey, but that their past experiences were not satisfactory. The study investigates professional development considering many aspects and proposes suggestions based on the findings.